Lamellar Morphology of an ABA Triblock Copolymer with a Main‐Chain Nematic Polyester Central Block. Issue 10 (19th April 2013) - Sato, Kazunori; Koga, Maito; Kang, Sungmin; Sakajiri, Koichi; Watanabe, Junji; Tokita, Masatoshi
Abstract A liquid crystal (LC) ABA triblock copolymer with poly(styrene) (PS) A blocks and a main‐chain nematic LC polyester B block is synthesized by atom‐transfer radical polymerization of styrene with an LC polyester macro‐initiator. The nematic LC and PS amorphous phases are segregated from each other to form lamellae with a spacing of 27 nm. The 16 nm‐thick nematic LC lamellae are significantly smaller than the contour length of the LC segment (63 nm), and the nematic director is parallel to the lamellae. The central LC segment is primarily more extended in the lamellar direction, but folds so as to meander through the LC lamella and bridges adjacent PS domains. The lamellar microstructure exhibits a reversible spacing increase of up to 31 nm with increasing temperature, suggesting a corresponding increase in the probability of the chain folding. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>